Alih Kode dan Campur Kode dalam Dialog Tokoh pada Cerita Webtoon “Day by Bae” Karya HAAI Episode 1-23 - Ulil Hestining Dyastuti; Asropah; Mukhlis (Ta'ehao: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
The study aims to describe the type and the factor behind code switching and code mixing to a story in the Webtoon application titled “Day by Bae” by HAAI from episode 1—23. The data being researched is a character dialogue in the story that contains the code switching and the code mixing. The study uses a qualitative descriptive approach. The documentation method aided by note technique and data card used as data collection. Classifying all the data acquired by the type and the factor in the cause is the data analysis technique in this study. The data analysis results are explained with a descriptive using informal techniques. The form of code switching and code mixing that found in the “Day by Bae” story amounts to 164 data. The speaker, the person with whom you speak, the presence of a third person, the change from informal to formal, and the changed topic of conversation are factors that have caused the code switching. On the contrary, the speaker and the speaker’s personality, used popular terms, and being just prestigious are some of the factors behind the code mixing.